Technological enablers and confidence building in end-users for effective non-domestic water demand management. Issue 6 (1st November 2020) - Seah, Harry; Lee, Nina
ABSTRACT: By 2060, 70% of Singapore's total water demand will be used for non-domestic purposes. Effective management of this demand will allow the national water agency, PUB, to achieve significant leverage and take strides in water sustainability as land use nears capacity limits in Singapore. Uptake of water conservation projects was sluggish in the initial years due to the high upfront capital and manpower resources required for implementation, and perceived incremental benefit to business margins. Through policy reform, technological innovation and a rigorous industrial engagement strategy, PUB has since completed 45 water conservation projects and is set to achieve 14.3 million gallons per day in non-domestic water savings by the end of 2020.